Chinese Economic Diplomacy before and during the COVID-19 Pandemic - E. I. Safronova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The process of globalization has turned international economy into an arena of direct and indirect conflict of interests of various actors. It has also provided states with a new tool for their foreign policy activity — economic diplomacy. The paper focuses on the economic diplomacy of the People’s Republic of China, which not only has become the second important center of the world economy, but is starting to realize its increased capabilities, demonstrating ambitions of a new leader in international relations. The first section outlines the main features of the PRC’s economic diplomacy. The second section focuses on the key areas and specific mechanisms of the so-called incentive economic diplomacy. In this regard, the author emphasizes two trends: on the one hand, China aims at effectively integrating into existing international formats and institutions of global economic governance, but, on the other hand, it shows willingness to take the lead and initiate its own ambitious projects. The Silk Road Fund and the Regional Comprehensive Economic Partnership (RCEP) as well as the mega-project ‘The Silk Road Economic Belt and the 21st-century Maritime Silk Road’ are the most striking examples of the latter trend. Incentive economic diplomacy also serves as an important tool for strengthening the soft-power potential of the PRC in the international arena, especially in developing countries. At the same time, the author stresses that in recent years the PRC resorts more actively to the use of offensive forms of economic diplomacy, such as sanctions. This trend is examined in the third section of the paper. The international crisis provoked by SARS-CoV-2 pandemic became a moment of truth and a stress test for the new foreign policy system of the PRC. The fourth section analyses new challenges faced by China’s economic diplomacy in the context of the pandemic. These challenges have both an objective (the need for quick national economic recovery) and subjective dimensions. The latter implies the wholescale information war as the PRC and the countries of the collective West led by the United States started playing blame game. The author notes that, under these circumstances the PRC’s ‘COVID-19 diplomacy’ becomes more aggressive, which negatively affects the already tarnished national image. However, the author concludes, that although the current Chinese economic diplomacy generates rather negative sentiments in both developed and developing countries, it is exactly economic diplomacy that could, if properly used, help the PRC to establish itself as a leading actor in the new bipolar world order.